2016
DOI: 10.1111/1365-2435.12777
|View full text |Cite
|
Sign up to set email alerts
|

Physiological maturity at a critical life‐history transition and flight ability at fledging

Abstract: Summary Developmental maturity (e.g. body condition, body mass) at major life‐history transitions is known to affect fitness across a wide range of taxa. Fledging (leaving the nest), a major life‐history transition in birds, is associated with high post‐fledging mortality and is widely assumed to be related to poor initial flight ability of fledglings, which, in turn, might be related to developmental maturity at fledging. We investigated individual variation in developmental maturity of both somatic and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…Future studies should focus on the post-fledging effects of hematophagous ectoparasites such as blowflies, particularly on the effects that decreased oxygen-carrying capacity due to reduced hemoglobin might have on flight performance in tree swallows and other aerial specialist hosts (Cornell et al 2017). Future work should also emphasize the importance of specific acquired immunity in bird-ectoparasite dynamics, and the degree to which heritability and maternal transfer of antibody response can influence these dynamics (Garnier and Graham 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should focus on the post-fledging effects of hematophagous ectoparasites such as blowflies, particularly on the effects that decreased oxygen-carrying capacity due to reduced hemoglobin might have on flight performance in tree swallows and other aerial specialist hosts (Cornell et al 2017). Future work should also emphasize the importance of specific acquired immunity in bird-ectoparasite dynamics, and the degree to which heritability and maternal transfer of antibody response can influence these dynamics (Garnier and Graham 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although hematocrit has its limitations as a sole measure of an individual's condition due to many sources of variation (Fair, Whitaker, & Pearson, ), anemia can lead to decreased oxygen transport to tissues that impact flight performance, and fledglings that continue to suffer from anemia could have reduced abilities to evade predators and reduced foraging abilities (O'Brien et al., ). A recent study in starling nestlings found that physiological maturity as indexed by both hematocrit and hemoglobin concentration lags behind somatic maturity at nest leaving, that there is greater variability in physiological traits associated with oxygen‐carrying capacity than with somatic measures of growth, and that both somatic and physiological maturity contribute significantly to models of initial flying ability at nest leaving (Cornell, Gibson, & Williams, ). We expect that any deficits associated with anemia in nestlings would persist until normal hematocrit levels are achieved, which might take several weeks given the slow renewal rates of red blood cell in birds (Rondan et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…European starlings, Sturnus vulgaris; Cornell et al, 2017), asymptotic mass (see Glossary) or size of chicks (somatic maturity) is attained at, or close to, fledging age (Starck and Ricklefs, 1998), i.e. chick growth continues throughout the nestling phase.…”
Section: Cost Of Reproductionmentioning
confidence: 99%